LC-MS/MS Content Analysis of Ethanol Extracts from Some Naturally Occurring Plants and Their Biological Activity Against Certain Plant Pathogenic Microorganisms Under In Vitro Conditions - Öğün, Erdal; Koç, İbrahim; Güral, Yunus; Aydoğmuş, Ercan; Özgen, İnanç (Hakkari Üniversitesi, 2025)
There is a significant need for environmentally friendly organic pesticides. This study was conducted to analyze the content of ethanol extracts from some naturally occurring plant parts in Elazığ, Türkiye, using LC-MS/MS and to determine their activity against certain plant pathogenic bacteria and microfungi. The study was carried out under in vitro conditions using a Randomized Complete Block Design with four replications. Antibacterial activity was assessed using the Agar Well Diffusion Method in Mueller-Hinton medium, while antifungal activity was determined using the Poisoned Food Method in Malt Extract Agar medium. The statistical analysis of the obtained data sets was performed using the Kruskal-Wallis H test. As a result, among the 33 standard compounds investigated in the extracts, none were found in Asphodelus aestivus L. and Melissa officinalis; three compounds vanillin, gentisic acid, chlorogenic acid) were identified in Tanacetum parthenium; and four compounds vanillin, trans-cinnamic acid, p-coumaric acid, hydroxybenzaldehyde) were identified in Rosa canina L. Rosa canina L. extract showed no activity against the pathogenic test microfungi, while the activity of Tanacetum parthenium extract increased with higher concentrations. It was observed that the extracts of Asphodelus aestivus L. and Melissa officinalis completely inhibited the growth of microfungi at concentrations of 15% and above(v/v).

Çevre dostu organik pestisitlere ciddi derecede gereksinim duyulmaktadır. Bu çalışma, Elazığ’da (Türkiye) doğal yayılış gösteren bazı bitki kısımlarının etanol ekstraktlarının LC-MS/MS ile içerik analizi, bitki patojeni bazı bakteri ve mikrofunguslara karşı aktivitesini belirleme amacıyla yapılmıştır. Çalışma, in vitro şartlarında Tesadüf Parselleri Deneme Deseninde ve dört tekerrürlü olarak yürütülmüştür. Antibakteriyel aktivite, Agar Well Diffüzyon Yöntemiyle Mueller-Hinton ortamında; antifungal aktivite, Poisoned Food Method kullanılarak Malt Ekstrat Agar ortamında belirlenmiştir. Elde edilen veri setlerinin istatistiksel analizinde Kruskal Wallis H testi kullanılmıştır. Sonuç olarak: Ekstraktlarda araştırılan 33 standart bileşikten Asphodelus aestivus L. ve Melissa officinalis’te rastlanılmadığı; Tanacetum parthenium’da üç (sırasıyla vanillin, gentisic acid, chlorogenic acid); Rosa canina L.’da dört (sırasıyla vanillin, trans-cinnamic acid, p-coumaric acid, ydroxybenzaldehyde) bileşik belirlenmiştir. Patojen test mikrofungusları üzerine Rosa canina L. ekstraktının aktivite göstermediği; Tanacetum parthenium ekstraktının artan konsantrasyonlarla birlikte aktivitesinin arttığı; Asphodelus aestivus L. ve Melissa officinalis ekstraktlarının %15 ve üzeri oranlarda (v/v) mikrofungusların çoğalmasını tamamen engellediği görülmüştür.
Doğal Yayılış Gösteren Bazı Bitkilerin Etanol Ekstraktlarının LC-MS/MS İçerik Analizi, İn Vitro Şartlarında Bazı Bitki Patojeni Mikroorganizmalar Üzerindeki Biyolojik Aktivitesi
Keywords: Plant Pathology; Bitki Patolojisi